AKIBAT HUKUM DIKELUARKANNYA IZIN LINGKUNGAN BARU MELALUI SURAT KEPUTUSAN GUBERNUR JAWA TENGAH NOMOR 660.130 TAHUN 2016 PASCA DIBATALKANNYA IZIN LINGKUNGAN NOMOR 660.117 TAHUN 2012 - Mardhatillah, Siti Ruhama (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2018)
Abstract Since the publishment of environment permit through Governor of Central Java Decision Number 660.1/30 of Year 2016 has caused any juridical problem because this environment permit replaces of the previous permit, that is Governor of Central Java Decision Number 660.1/17 of Year 2012 which has been canceled by the earlier Supreme Court Decision Number 99/PK/TUN/2016. The problem formulation of this research is how the legal consequences through the publishment of the last environment permit after cancellation the previous environment permit by the Supreme Court. This research is juridical-normative research with using conceptual and statute approach. The result of the research is the legal consequnces through the publishment of last environment permit is that permit can be cancelled (vernietigbaar), so that all the consequences during the enactment of that permit are legitimate until the revocation by Governor of Central Java Decision Number 660.1/4 of Year 2017. Key words: Legal consequences, Environment Permit Number 660.1/17 of Year 2012, Environment Permit Number 660.1/30 of Year 2016.